SZ_GERICHTE STK 2023 60 vom 19. August 2025 , Aussetzung, evtl. Unterlassung der Nothilfe, Landesverweisung - SZ Gerichte (2025)
Aussetzung, evtl. Unterlassung der Nothilfe, Landesverweisung | Strafgesetzbuch